Implementation E-Learning Based Moodle on Physics Learning in Senior High School - Suritno - Fayanto; Maria Yosephien Retna Tinon Kawuri; Adi Jufriansyah; Danur Dara Setiamukti; Dwi Sulisworo (Indonesian Journal of Science and Education (IJOSE), 2019)
The problems faced today by Indonesian teachers are the difficulty of implementing e-learning in the learning process, especially physics learning. During this time the teacher considers using e-learning in the classroom will not be effective. This study aims to explain how the implementation of physics learning by using Moodle-based e-learning in the learning process. In this study, it divided into two aspecs, namely learning outcomes and interest in learning with physics learning material in rectilinear motion. This study uses an experimental class design with a sample size  X class of 10 students of Public High School 1 Piyungan group chosen randomly. This study used the design of one group pretest and posttest using the T-Test while the significance value using N-gain analysis scores and learning interests obtained from the questionnaire. The results of the analysis show an increase in learning outcomes with very high N-gain significance values. Then the percentage of student learning interest reaches 66% which is in the excellent category. So it can be concluded that the application of moodle-based learning can increase learning interest and learning outcomes and 73% of students agree if knowledge based on Moodle applied in the learning process. Keywords: e-learning, Moodle, learning management system, learning outcomes, interest in learning